The Image of Antique Philosopher Diogenes in John Amos Comenius' Play for XVII Century School Theatre - Svetlana Mashevskaya (Hypothekai, 2018)
Antique dramaturgy appears to be one of the sources for the emergence of School theatre. The article considers the primary stage of this process in the XVIth century. The use of ancient themes by school dramaturgists in the middle of the XVIIth century is shown on the example of J.A. Komensky’s play about Diogenes of Sinope. The source materials about Diogenes that were avaliable to J.A. Komensky are analized; the article also defines the place of ancient thematics in Latin school programmes, including Komensky’s pansophical school, as well as his ambiguous attitude towards ancient authors in educational process and on the school theatre stage.By comparing the image of Diogenes of Sinope in D. of Laertes’s treatise and Komensky’s play, the author comes to the conclusion that the interpretation of Diogenes image by Komensky starts with the selection of material for the play and sequencing it in chronological order. The article presents a summary of the play. The play covers the entire life of the main character, which is not typical of the XVIIth century school plays. From the very beginning, Diogenes behaves like a repentant, no longer willing to take a path of fraud, a religious person, reasonably estimating his own possibilities and skills, somewhat ambitious and convinced that one should emulate “smart people, who managed to turn accidents into a cause for valor”. He is optimistic and thinks that, perhaps, he is the one who will manage to learn philosophy even though he doesn’t have the financial means. Diogenes is willing to “endure hunger, thirst, pain and exhaustion”, which he got used to during his travel, “just to become an educated person”. During the play, a major feature of Diogenes the Cynicist is revealed to live in full accordance with his own philosophy. By comparing the similar thoughts of Diogenes and Komensky, and those ideas that were introduced into the play by Komensky, we come to realization, that the playwright makes use of the available material freely and resourcefully. The author’s thoughts are implemented into a story of Diogenes’ life in such a way that, as a result, the play represents an organic synthesis of Antique and Baroque, the thoughts of both Diogenes of Sinope and J.A. Komensky. That is what also distinguishes it among other plays of the XVIIth century. The play is devoted to fighting with vices and the triumph of the good. That is what the cynic philosopher fought for, that is what the great pansophist, who revealed to us the path of ‘’redeeming the acts of humanity”, dedicated his life to. The article also presents a brief history of the play “Diogenes” and its major publications and translations. The image of Diogenes in J.A. Komensky’s play is an example of a baroque principle of combining the uncombinable. In the image, an ancient philosophercynic and an ideal philosopherpansophist are joined together.